Application of the Chinese version of Zelaya's HIV-related stigma scale to undergraduates in mainland China - Fang Ruan; Guochen Fu; Mingyu Zhou; Lan Luo; Jing Chen; Wei Hua; Xin Li; Yifan Chen; Xiaobao Xia; Yanting Xiong; Yuhua Chen; Bin Shi; et al. (BMC, 2019)
Abstract Background This cross-sectional study aims to validate the Chinese version of Zelaya's HIV-related Stigma Scale (CVZHSS) among a large undergraduate sample in mainland China, and apply it to measure the level of different dimensions of stigma and their respective determinants. Methods From September 10, 2018, to January 9, 2019, a total of 10,665 eligible undergraduates conveniently drawn from 30 provinces in mainland China (except for Tibet) completed the self-designed online questionnaire distributed via sojump.com voluntarily, anonymously and confidentially. Both exploratory and confirmatory factor analyses (EFA and CFA) were first performed to test its construct validity, Cronbach's alpha was then used to assess its internal consistency, and Logistic regression analyses were finally carried out to identify predictors of various dimensions of stigma. Results As expected from the original model, four factors (i.e., "fear of casual transmission", "moral judgment", "personal stigma" and "perceived community stigma") were extracted using principal component analysis with varimax rotation, accounting for 63.26% of the total variance. The CFA further confirmed the four-factor construct (CFI = 0.92, GFI = 0.91, RMSEA = 0.07). In addition, all the four factors demonstrated acceptable internal consistency with Cronbach's alpha ranging from 0.83 to 0.92. Stigma as measured by "fear of casual transmission" (74.4%), "moral judgement" (61.6%), "personal stigma" (79.0%) and "perceived community stigma"(36.5%) is highly prevalent among undergraduates. Except for non-freshmen, less knowledge about HIV and unsafe sex which were consistently associated with higher levels of stigma in all four dimensions, other eight variables including gender, residential area, major, sexual orientation, having ever being tested perception of HIV risk, willingness to utilize HTC service and awareness of the national AIDS policy played differential roles in affecting different dimensions of stigma. Conclusions The CVZHSS is a reliable and valid measurement tool and can be used to identify undergraduates with high levels of stigma. However, the four dimensions (Fear, moral judgement, personal stigma and perceived community stigma) were respectively influenced by different determinants, and thus should be treated independently when designing, implementing and evaluating stigma reduction programs.